Double-Leaf Infill Masonry Walls Cyclic In-Plane Behaviour: Experimental and Numerical Investigation - Furtado, André (2018)
Background: The infill masonry walls are widely used in the construction of reinforced concrete buildings for different reasons (partition, thermal and acoustic demands). Since the ‘60s decade, one of the most common typology in the southern Europe was the double-leaf infill walls. Recent earthquake events proved that this specific typology have an important role in the seismic response of reinforced concrete structures in terms of stiffness, strength and failure mechanisms. However, modelling approaches of these specific infill panels cannot be found over the literature. Objective: Due to this, the major goal of the present manuscript is to present a simplified modelling strategy to simulate the double-leaf infill masonry walls seismic behaviour in the software OpenSees. Method: For this, two different modelling strategies were proposed, namely through a global and an individual modelling of the panels. An equivalent double-strut model was assumed and both strategies were compared and calibrated with experimental results from a full-scale in-plane test of a double-leaf infill masonry wall. Results: The numerical results obtained by each strategy are very accurate in terms of prediction of the specimen’ initial stiffness, maximum strength and strength degradation. Conclusion: From the force evolution throughout the tests, it was observed differences lower than 10%. Globally, the individual modelling approach reached better results.